Frasa Numeralia dalam Bahasa Batak Toba - Lilis Handayani Napitupulu (BIP: Jurnal Bahasa Indonesia Prima, 2022)
Every language featured numeral as part of its syntactic system. It is not unreasonable, then, to assume that numerals are one place where cross-linguistic comparisons are especially fruitful and syntactic universals may be uncovered. However, once these systems are examined more closely, the picture becomes a lot more complicated, for it appears that numerals do not belong to a uniform syntactic category. This article is a descriptive analysis of the syntactic category which discussed the numeral phrase structure in the Toba Batak language. The study of this phrase structure applied generative syntax sub-theory; X-bar theory. The research method was from written resources, the distributional method, and intensifying technique. The data analysis results showed numeral phrase structure in the Toba Batak language consists of complement, specifier, adjunct, and nucleus.